2021
DOI: 10.1093/pm/pnab247
|View full text |Cite
|
Sign up to set email alerts
|

Are Positive Psychology Interventions Efficacious in Chronic Pain Treatment? A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective Although positive psychology interventions are increasingly popular in chronic pain treatment their efficacy is still unclear. The objective is to summarize evidence on the effect of positive psychology interventions (PPIs) on pain, physical functioning, and emotional functioning in adults with chronic pain. Methods Four electronic databases and additional references were searched for randomized controlled trials pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
5
29
0
1
Order By: Relevance
“…A meta-analysis of 29 observational and experimental studies documented a protective effect of PA on pain severity in adults with chronic non-cancer pain [26]. These findings are in line with a recent systematic review and meta-analysis of randomized controlled trials (RCTs) showing beneficial effects of positive psychology interventions (PPI) in chronic pain treatment [27]. Thus, evidence supports applying PPIs in the treatment of chronic 4 pain [27,28], yet the implementation of PPI approaches into clinical practice has been slow and varied [19,20].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…A meta-analysis of 29 observational and experimental studies documented a protective effect of PA on pain severity in adults with chronic non-cancer pain [26]. These findings are in line with a recent systematic review and meta-analysis of randomized controlled trials (RCTs) showing beneficial effects of positive psychology interventions (PPI) in chronic pain treatment [27]. Thus, evidence supports applying PPIs in the treatment of chronic 4 pain [27,28], yet the implementation of PPI approaches into clinical practice has been slow and varied [19,20].…”
Section: Introductionsupporting
confidence: 73%
“…These findings are in line with a recent systematic review and meta-analysis of randomized controlled trials (RCTs) showing beneficial effects of positive psychology interventions (PPI) in chronic pain treatment [27]. Thus, evidence supports applying PPIs in the treatment of chronic 4 pain [27,28], yet the implementation of PPI approaches into clinical practice has been slow and varied [19,20]. Potential barriers include high patient burden associated with privacy concerns, time, and mobility or travel limitations [18,29].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Studies in people with chronic pain show that positive affect may be depleted during pain and stress, and that positive affect inversely predicts pain reports (Zautra, Fasman, et al, 2005;. Moreover, positive psychology interventions have been shown to successfully promote positive affect, wellbeing and functioning, and reduce pain severity and depression in individuals suffering from chronic pain [see Ong et al (2020) and Braunwalder et al (2022) for systematic reviews].…”
Section: Positive Affectmentioning
confidence: 99%
“…Because of its assumed contribution to chronic pain disability, investigating ways to mitigate avoidance overgeneralization may help optimize therapies. Increasing evidence shows that it may be beneficial to target positive affect in pain treatment (Finan & Garland, 2015;Hanssen et al, 2017); positive psychology interventions successfully augment positive affect, wellbeing and functioning, and reduce pain severity and depression in individuals with chronic pain (Braunwalder et al, 2022;Ong et al, 2020). Geschwind et al (2015) showed that experimentally induced positive affect is associated with less generalization of pain-related fear.…”
Section: Introductionmentioning
confidence: 99%